Phenylsilane as an effective desulfinylation reagent - Midura, Wanda H.; Rzewnicka, Aneta; Krysiak, Jerzy A. (Beilstein Journal of Organic Chemistry, 2017)
The reduction using phenylsilane in a KOH-catalyzed system was applied successfully to the conversion of sulfinyl-substituted cyclopropylcarboxylates into the corresponding alcohols. The presence of sulfinyl substituents in the α-position to the carboxylate group caused a desulfinylation product formation with full regio- and stereoselectivity, instead of a carbonyl group reduction. Investigations performed on different α-sulfinylcarbonyl compounds revealed that phenylsilane treatment constitutes a regiospecific method for the desulfinylation of a-sulfinylesters; for corresponding ketones the reaction course depends on the character of the carbonyl group.
Keywords: desulfinylation; phenylsilane; reduction; regioselectivity; α-sulfinylesters